Buying and Selling Marijuana Coffee in Cross Medan, Southeast Aceh Perspective of DSN MUI Fatwa No.110/DSN-MUI/IX/2017 - Al Syifa, Khairunnisa; Efendi, Rahmad (Dinasti Research, 2024)
Buying and selling is an agreement to exchange goods that has benefits for the user. In its implementation, buying and selling must be based on the provisions of Islamic law, in that it does not contain elements that are forbidden, because of Allah SWT. has permitted buying and selling and prohibited usury. The concept of buying and selling in Islam encourages transactions that are honest, fair and beneficial to both parties as well as maintaining a good relationship with Allah and gaining His approval. The practice of buying and selling marijuana coffee across Medan, Southeast Aceh violates legal regulations. Of course, coffee can be consumed halally, but not marijuana. The combination of coffee and marijuana is a problem whether this type of drink is halal for consumption, in the perspective of DSN MUI Fatwa No.110/DSN-MUI/IX/2017 concerning Sale and Purchase Agreements. If buying and selling marijuana coffee is carried out then this buying and selling is not valid according to Islamic law because there are elements of haraam which are prohibited both by religion and by law in Indonesia. The research method used is an empirical juridical method, namely field research, using a qualitative approach.